Fabelvejen mod nord: Merethe Lindstrøms Nord (2017) som besjælet dystopi - Auklend, Morten (Passage - Tidsskrift for litteratur og kritik, 2019)
Merethe Lindstrøm’s novel Nord [North] (2017) deals with end time-themes. The novel formally departs from mainstream science fiction and apocalyptic fiction by providing flashes of the past and the present in concentrated lyrical images that are repeated throughout the novel. Through poetic rituals and ceremonies, and in metaphorical patterns of personification wherein a devastated nature comes ‘alive’, a world is reborn rhetorically and the reader is forced to ponder the abilities and qualities embedded in an overwhelmingly poetical language. By focusing on the demarcation of literal and figurative language and the transcendence of poetic images of nature, the novel becomes a contemplation of individuals coping with questions concerning identity and remembrance in an inhuman world. The article demonstrates how devices and perspectives provided by science fiction can provide strong thought for hard times.